Semiconductor-metal-oxide-based nano-composites for humidity sensing applications. (February 2023) - Kumar, Ankit; Gupta, Gaurav; Bapna, Komal; Shivagan, D.D.
Highlights: Basic characteristics of humidity sensing and humidity generation methods are illustrated. Presents humidity sensors based on SMO nanostructures and composites with recent developments. Influence of material engineering in humidity sensors is elaborated. Interaction of water molecules on surface of different SMOs is demonstrated. Discussed the possibility of Flexible SMO humidity sensors for future wearable devices. Abstract: Humidity sensing is of great significance in agriculture, pharmaceutical, medical, environmental, etc. Among various types of materials, semiconductor metal oxides (SMOs) are widely studied as humidity sensors due to their easy fabrication, chemical inertness, low-cost and portability. The review presents the humidity sensors based on various SMO nanostructures and their composites with the recent developments. Basic sensing characteristics of a humidity sensor, relative humidity generation methods, sensing mechanism and influence of material engineering are illustrated. The review elaborates the theoretical aspects of water adsorption and the experimental outcomes. It is revealed that there are still challenges to achieve humidity sensors with best of all sensing characteristics, to bring them into practical applications. The possibility of flexible SMO nano-composites for wearable devices in healthcare sector and artificial intelligence is discussed. The review is concluded with the gap and ideas for future developments of these SMO nano-composites for dynamic humidity sensing applications. Graphical abstract: Image, graphical abstract